Influência das inundações na distribuição de espécies arbóreas ao longo do Rio Massaguaçu (Caraguatatuba, São Paulo, Brasil), e potencial alelopático de Annona glabra L - Matsumoto, Reginaldo Sadao (2009)
The vegetation of blind estuary of the Massaguaçu River in Caraguatatuba, is subject to periodical flooding. This flooding regime may be an important factor over the local tree composition and distribution. The present research purpose was to determine the tree-shrub species distribution on the Massaguaçu river estuary, related to flooding regime. Upstream, from the river mouth, 5 flooded vegetation banks were established (A, B, C, D, e E). Eighty plots (5x5m) were sample drew in each field, in which, quantitative and qualitative tree shrub (PBH>10 cm) species were sampled. Annona glabra L basal perimeter and height measurements were collected. Central plot deep were measured, as well the estuary daily water level. The rainy season estuary open-close cycle are more frequent and have a higher average maximum level. Caraguatatuba total field have a 2.216 nat.ind.-1 Shannon diversity index and 30 species total richness. The most richer was the Myrtaceae family. A and C plots were more similar among themselves as well D and E plots. In despite of species adaptations to periodic flooding, higher richness was found in lower flooded ranges. The species distribution per average deep plots shows Annona glabra, Dalbergia ecastophyllum, Hibiscus pernambucensis and Garcinia gardneriana occupying deeper sites than other species. A. glabra biometric prameters indicate higher and more thin trees, when in association with other species, than living in mono specific groups. The water depth regime limits the species distribution and composition in Massaguaçu river estuary. The A. glabra distribution seems to be related to their flooding adaptations and to their colonization in less competitive spots.